Brand Satisfaction, Brand Trust and Brand Loyalty : The Mediating Role of Brand Performance and The Moderating Role of Market Rationally in Culinary Industry - Ambarwati, Diana; Sudarmiatin; Indah Yuni Astuti (Formosa Journal of Applied Sciences, 2024)
This research aims to determine whether brand performance predictions have a direct influence on brand loyalty, brand satisfaction and brand trust have a direct influence on brand loyalty, brand satisfaction and brand trust have a direct influence on brand performance and rational market have a direct influence on brand loyalty and market rationally in moderating brand satisfaction and brand trust directly on brand loyalty and brand performance predictions in mediating brand satisfaction and brand trust indirectly on brand loyalty at CV. Wijaya Kembar. The population and sample of 150 customers who bought brand products Wijaya Kembar in March 2024 are used in this quantitative study. This study employed a questionnaire for data collection, and SmartPLS3 was used for analysis. The results showed that market rationality cannot moderate the influence of brand satisfaction and brand trust directly on brand loyalty; market rationality has no direct and negative influence on brand loyalty; brand performance cannot mediate the influence of brand satisfaction and brand trust indirectly and negatively on brand loyalty; brand trust does not have a direct or positive effect on brand loyalty and brand performance; and brand trust does not have a direct or positive effect on brand loyalty but has a direct and positive effect on brand performance variable. at CV. Wijaya Kembar.